Nepal Earthquake Post Disaster Needs Aassessment : Sector Reports - World Bank Group (World Bank, Washington, DC, 2015)
The post disaster needs assessment (PDNA) assesses the impact of the April 25, 2015 earthquake in Nepal and defines a recovery strategy. In the analysis, damage is defined as the cost to replace durable physical assets (buildings, equipment, facilities, and machinery) that were damaged or destroyed. Loss refers to changes in financial flows due to the temporary absence of infrastructure, increased or new demands (operational costs) due to the disaster, lost revenues, higher expenditures, and the cost of maintaining service provision. In addition to reconstruction costs, recovery needs are identified to build back better and are costed accordingly. Each sector has also examined issues of vulnerability and marginalization, and the need for specific targeting in the implementation of the recovery strategy. The report covers the following sectors: social; productive; infrastructure; and cross‐cutting.